A Discourse on the Atheism within the Malaysian Society - Wan Haslan Khairuddin,; Muhammad Hazim Baderun,; Abdull Rahman Mahmood, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Belief in God is the first of several principles enshrined in the Rukun Negara of Malaysia which makes it one of the important principles to be upheld by any Malaysian citizen. However, there are some who do not accept this concept of believing in God and they are referred to as atheists. The existence of this group can seen clearly when issues that concern this group became public knowledge like the meeting of atheists in Kuala Lumpur that took place in 2017 and the existence of a Facebook group called Warung Atheist (Atheist Stall). Therefore, this article is prepared to discuss a discourse on the atheism within the Malaysian society including: [1] to analyze past studies related to the definitions and history of atheism; [2] to analyze past studies related to atheist thoughts and arguments and [3] to analyze past studies related to the response and objection to atheism. This article is written using qualitative method with content analysis design. In general, the research findings show that, in Malaysia, there are so few studies conducted on this topic. The study on the definitions and history of atheism among Malaysian researchers is still lacking because many researchers make the studies as a side topic only. This also happens to studies on themes related to atheism, but it should be noted that there are several studies have begun to make focusing on atheism. However, most researchers in Malaysia conduct studies which concern the objection against and criticism towards atheism.